Normal and abnormal features of the lumbar spine observed in dual photon absorptiometry scans - Hopkins, A; Zylstra, S; Hreshchyshyn, M M; Anbar, M (Clinical nuclear medicine, 1989)
Dual photon absorptiometry (DPA) is an extensively used technique for measuring the density of the lumbar spine. The presence of vertebral and extra-vertebral pathologies can lead to increased scatter of data and artifactual bias when constructing diagnostic reference value curves. The bone density of patients with such abnormalities cannot be compared with those of normals because it will appear artificially high. Furthermore, little effort has been made to identify and evaluate spinal abnormalities using the pictograms produced in this method. We have analyzed 60 DPA scans for morphologic changes, using x-rays for comparison, and have found practically complete concurrence between these two radiologic methods on features, though only the former is capable of accurately quantifying bone density. Examples of DPA presentation of anatomical morphology are shown to aid the user in interpreting DPA findings.